A transversal and practical education as a business success factor: literature review of learning process of basic design through ICT tools - Javier Turienzo (Journal of Management and Business Education, 2024)
The ongoing societal transformation propelled by innovation and digitalization is amplifying the demand for technological adeptness among current and upcoming professionals. Consequently, there's a pressing need to revamp the educational system and its methodologies to elevate the requisite skill set. Spatial reasoning, innovative thinking, and creativity stand as pivotal proficiencies essential for enabling future professionals to swiftly craft adaptable prototypes catering to client needs. However, conventional teaching approaches exhibit shortcomings in nurturing spatial reasoning, necessitating deeper exploration within the realm of education. This study delves into novel 3D design tools aimed at facilitating three-dimensional modelling within educational settings. The findings underscore the imperative use of digital tools in crafting 3D objects, fostering the development of spatial visualization skills. Moreover, they emphasize the significance of intertwining ICT knowledge, programming skills, and pertinent soft skills. Such an amalgamation equips future professionals with enhanced work capabilities, a comprehensive grasp of market needs, and refined product commercialization strategies.